Gamification und Machinema als Unterrichtskonzepte. Eine Fallstudie am Beispiel der L3-Germanistikstudenten der Universität Algier 2 - Aid Naima (Aleph, 2024)
Learning a foreign language is a challenging task for many students. Especially in foreign language lessons, teachers are looking for innovative and effective methods to support the learning process and to increase the interest and motivation of the students. In this context, didactic language learning games such as Gamification and Machinima have proven to be a promising approach to make lessons more lively and interactive. The use of language learning games offers numerous potential advantages in DaF lessons. First, they can increase student motivation by making the teaching process fun and interactive. Secondly, they enable improved language skills, since the students can apply and consolidate their language skills in authentic and playful situations. In addition, language learning games encourage interaction and communication between students, which can lead to more intensive language use and a deeper understanding of the language. Finally, they can enrich the classroom by introducing variety and fun, which has a positive impact on learning